Assessment of waste tyre pyrolysis oil and oxy-hydrogen gas usage in a diesel engine in terms of energy, exergy, environmental, and enviroeconomic perspectives - Özer, Salih; Gülcan, Halil Erdi; Çelebi, Samet; Demir, Usame (Elsevier Ltd, 2024)
Nowadays, alternative fuel research is increasing day by day due to the restrictions imposed on internal combustion engines. Using waste tyres as fuel will positively contribute to the national economy and environmental impact. Using oxy-hydrogen (HHO) gas, will help improve engine performance and exhaust emissions. This study focuses on the energy, exergy, environmental, and enviroeconomic impacts of using diesel, WTPO, and HHO gas. Experiments were carried out at constant 3000 rpm with torque values of 1.6 Nm, 3.2 Nm, 6.4 Nm, 7.9 Nm, and 12.8 Nm. The experiments were initially conducted with 100% base diesel fuel, followed by tests with diesel/WTPO blends (various proportions of WTPO at 20%, 40%, and 60% by volume), diesel-HHO gas (at different flow rates of 5 L/min and 10 L/min) dual-fuel application, and finally, diesel/WTPO-HHO dual-fuel application. When the results are examined, the highest first (approximately average 24% increase) and second law efficiencies (approximately average 13% increase) compared to basic diesel fuel were achieved with Diesel+10 L/min HHO dual fuel. The addition of WTPO to diesel fuel caused a decrease in both first and second-law efficiencies; however, using a Diesel/WTPO blend with HHO gas contributed to a maximum average increase of approximately 17% and 7% in first and second-law efficiencies, respectively. Furthermore, the maximum reduction in exhaust energy (approximately an average 12%) was achieved with a diesel blend containing 60% WTPO fuel by volume. Adding WTPO fuel to diesel fuel has contributed to a decrease in environmental and enviroeconomic impact. The maximum decrease in environmental and enviroeconomic impact (averaging 9%) was achieved with a diesel blend containing 20% WTPO fuel by volume. © 2024 Hydrogen Energy Publications LLC
Keywords: Diesel fuel; Exergy and enviroeconomic analyses; Oxy-hydrogen gas; Waste tyre pyrolysis oil